Pentingnya Pemahaman Terhadap Ragam Bahasa dalam Meningkatkan Aksesibilitas dan Kualitas Layanan Publik - Fahma Sania Anggraini P. N; Ainun Nisa Fahdila; Syifa Puspita Sanjaya; Eni Nurhayati (Journal of Creative Student Research, 2024)
Public officials must be able to communicate and be responsive in a variety of languages ​​to improve their ability to produce public communication content that is interesting, more concise, contained, innovative and creative. Understanding various languages ​​is very important to master, because Indonesia consists of many tribes, each tribe has its own language. Language must be accompanied by ethics and norms. Ease of accessibility and public services in various languages ​​is very important to increase information openness and increase public participation in the decision-making process. In this way, the government can increase information disclosure and increase the public's ability to access information that is relevant to their needs.